FORMULASI TABLET EKSTRAK KULIT BIJI DURIAN (Durio zibethinus L.) DENGAN METODE GRANULASI BASAH MENGGUNAKAN PATI BIJI DURIAN (Durio zibethinus L.) SEBAGAI BAHAN PENGIKAT TABLET - Muhammad Amirul Wildan (E-Jurnal Kajen, 2023)
Durian (Durio zibethinus L.) is one of the tropical fruits that is favored by the public. Durian fruit consists of fruit flesh, seeds, and skin. The part that is consumed is the fruit flesh, while the seeds and skin are waste that will be thrown away. Durian seeds have an amylopectin content of 66.33%, with the high amylopectin content in durian seeds being the basis for using durian seed starch as a tablet binder. This study aims to determine the potential of durian seed starch as a binder in tablet preparations and the effect of using durian seed starch as a binder on the physical properties of tablets. The manufacture of durian seed skin extract tablets uses the wet granulation method. This study uses five formula designs with different concentrations of durian seed starch. The data analysis conducted in this study was to determine the potential effect of durian seed starch as a binder in tablet preparations and the effect of using durian seed starch as a binder on the physical properties of tablet preparations. Durian seed starch can be used as a binder in tablet preparations.